1999
DOI: 10.1007/pl00005356
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between uptake2 and rOCT1: effects of catecholamines, metanephrines and corticosterone

Abstract: Active and specialized transmembrane transport systems are responsible for the functional inactivation of catecholamines. Uptake2, the classical extraneuronal uptake system, and rOCT1, a recently cloned organic cation transporter, share a number of properties. The present study was undertaken to investigate putative differences between these two transporters that might clarify their relative physiological roles. Uptake of [3H]MPP+ ([3H]1-methyl-4-phenylpyridinium) by Caki-1 cells (to study uptake2) and by prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…All kinetic data correlated well with what has been previously reported for OCT3 in Caki-1 cells and other model systems for OCT3 [15, 20]. The uptake was further characterized to be carrier-mediated by the significant decrease in the uptake observed at 4°C.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…All kinetic data correlated well with what has been previously reported for OCT3 in Caki-1 cells and other model systems for OCT3 [15, 20]. The uptake was further characterized to be carrier-mediated by the significant decrease in the uptake observed at 4°C.…”
Section: Discussionsupporting
confidence: 76%
“…Decynium-22, a known selective inhibitor of OCT3, was chosen to confirm the [ 3 H]-MPP + uptakeobserved was mediated by OCT3. An IC 50 of approximately 0.05 µ M was determined, correlating well with what has been previously published in the literature [15]. …”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…This is important, because, while normetanephrine is a potent inhibitor of OCT3-mediated transport (Martel et al, 1999), it has been reported to have other pharmacological effects, including weak agonist actions at alpha-1 adrenergic receptors (Langer and Rubio 1973) and lowaffinity antagonism of alpha-2 adrenergic receptors (Lenz et al, 1991). The present findings indicate that, to the extent that these secondary pharmacological effects occur, the regulation of cocaine-induced reinstatement by normetanephrine is likely the result of OCT3 blockade, thereby validating the use of this compound as a pharmacological tool for studying OCT3-mediated processes.…”
Section: Discussionmentioning
confidence: 99%
“…OCT2 is predominantly expressed in the kidney in rodents and humans. In rat kidney, rOCTs are expressed in the basolateral membrane of the S1 and S2 segments (rOCT1) and S2 and S3 segments (rOCT2) of the proximal tubule, and they have a significant role in the first step of tubular secretion (Martel et al, 1999;Chen et al, 2002;Slitt et al, 2002). A study using OCT gene-disrupted mice demonstrated that the kidney-to-plasma concentration ratios of prototypic organic cation tetraethylammonium (TEA) in OCT1(Ϫ/Ϫ), OCT2(Ϫ/Ϫ), and OCT1/2(Ϫ/Ϫ) mice at steady state were 2-, 2-, and 6-fold lower, respectively, than that in wild-type mice, suggesting that both OCT1 and OCT2 are involved in the uptake of TEA by the kidney (Jonker et al, 2003).…”
mentioning
confidence: 99%